2020
DOI: 10.35631/ijmoe.25003
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning and Teaching Using Kahoot!

Abstract: There are various technological tools and software that can be used to enhance the language teaching-learning process. Research has shown that the integration of ‘gamification’ based software like Kahoot! has the ability to influence and enhance language learning outcomes and can be used as effective teaching and assessment tools in language classrooms. This study explores the language teaching and learning experiences of five teachers and 50 secondary students in an international school when they used Kahoot!… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
(14 reference statements)
1
15
0
1
Order By: Relevance
“…The data analysis also demonstrated that high involvement was observed during online classes, implying that the use of Kahoot in lessons resulted in an increase in final grades. In addition to that, Kaur and Nadarajan (2020) revealed that almost all the students had favourable experiences with Kahoot!. Kahoot!…”
Section: Past Studies On Online Quiz Toolsmentioning
confidence: 79%
See 1 more Smart Citation
“…The data analysis also demonstrated that high involvement was observed during online classes, implying that the use of Kahoot in lessons resulted in an increase in final grades. In addition to that, Kaur and Nadarajan (2020) revealed that almost all the students had favourable experiences with Kahoot!. Kahoot!…”
Section: Past Studies On Online Quiz Toolsmentioning
confidence: 79%
“…The use of technology in learning and teaching has proven to be an effective way of connecting with students' learning styles. Every kid had different learning styles and technology allows teachers to accommodate these differences (Bernard et al, 2017) as cited by Kaur and Nadarajan (2020). Furthermore, the use of technology can shift old passive learning models into more active learning modes allowing dynamic teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…Kahoot! Game is a reply framework-based game played in real-time (Kaur & Nadarajan, 2020). There are three purposes for using Kahoot!…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using Kahoot as an ice breaker also helps teachers to assess their students indirectly. Kaur and Nadarajan (2020) shows that Kahoot is enjoyable assessment tool. It is shown through a study where the participants report their perspectives on the use of Kahoot.…”
mentioning
confidence: 99%
“…The study uses experimental research design and it is found that the significant value is 0.02, it is lower than the significant level 0.05. it can be inferred that Kahoot is effective in influencing students' reading skills. However, Kahoot is believed as an attractive game-based features for students particularly if it is used in language learning activities that allows students to explore their language skills with their mates or peers synchronously and get an actual reaction (Kaur & Nadarajan, 2020).…”
mentioning
confidence: 99%